Calcium effect on the Kraft pulp delignification of Eucalyptus dunnii, Eucalyptus globulus and Eucalyptus grandis - Fariña, Ismael (2014)
Previous studies indicate that in Populus tremula and Betula pendula the cooking process could be affected by calcium content. It is suggested that calcium ions decrease Kraft delignification rate by formation of calciumlignin interaction, which lead to decrease solubility of lignin during the process. In Eucalyptus globulus, formation of different bindings between calcium and substances released from this species during Kraft cooking delignification is exposed as explanation for the absence or reduction of the calcium effect. The Eucalyptus genus in Uruguay is considered a heavy consumer of soil nutrients due to its high growing rate, even though appreciable variations in nutrient content exists between different Eucalyptus species and within the same species. This work studies the calcium effect on Kraft delignification in five Eucalyptus dunnii, four Eucalyptus globulus and three Eucalyptus grandis of different age, soil type and geographical Uruguayan areas, and determines the content of calcium and phosphorus in wood, pulp and black liquor. Results suggest that there is a detrimental influence of calcium on the performance of the Kraft process in the Eucalyptus genus since higher wood calcium content gives lower yield at constant Kappa number, and higher Kappa number and lower ISO brightness at constant cooking conditions. Important differences among species were found in wood calcium content, E. dunnii presented higher values and a wider range than E. globulus and E. grandis, so the calcium detrimental effect in Kraft process is clearer observed in E. dunnii samples. Moreover three Eucalyptus samples were chosen to perform an acid leaching previous Kraft process, in order to compare the cooking behavior with and without metals extraction, these results indicate that not appear to be this procedure a suitable way to remove calcium from Eucalyptus wood, at least for samples used in this work and especially in cases with high wood calcium content.